ASSESSMENT OF LEFT VENTRICULAR SYSTOLIC AND DIASTOLIC FUNCTION BY TISSUE DOPPLER IMAGING AFTER ACUTE MYOCARDIAL INFARCTION - Rahman, Hafiz ur; Khan, Sher Bahadar; Noor, Lubna; Hadi, Abdul; Nawaz, Tariq; Shah, Syed Tahir; Abbas, Farhat; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2011)
Objective: To evaluate left ventricular systolic and diastolic function by Tissue Doppler imaging after acute myocardial infarction. Methods: It was a hospital based, prospective descriptive study, from 1st July 2010 to 31st Dec. 2010. Total of 200 patients having acute myocardial infarction underwent detailed tissue Doppler imaging (TDI) echocardiographic examination for evaluation of left ventricular systolic and diastolic function on day 3, in echocardiographic section of Govt. Lady Reading Hospital, Peshawar. Peak systolic (Sm), peak early diastolic (Em) and peak late diastolic (Am) velocities were recorded at 4 different sites of the mitral annulus. The ejection fraction and pulse wave TDI diastolic parameters were also recorded. Using SPSS version 16 data was analysed, frequencies and Mean±SD were determined for categorical and numerical variables, respectively. A p-value ‰¤0.05 was considered significant. Results: Total study sample was 200 patients having acute myocardial infarction (MI). The sample was divided into 4 groups, i.e., anterior MI, inferior MI, septal MI, and lateral MI. There were 122 men and 78 women and the mean age was 42±5 SD. There was a marked reduction in Sm velocity at mitral annulus, especially at the infarction sites. The mean peak systolic velocity from 4 mitral annulus sites was well correlated with ejection fraction (p=0.0001). Similar to systolic velocities, Em velocity was also reduced, especially at the infarction sites. The mean peak early diastolic velocity from 4 mitral annulus sites was well correlated with ejection fraction (p=0.0001). The mean Em velocity was correlated well with isovolumic relaxation time (IVRT). There was no correlation between mean Em velocity and deceleration time (DT). Conclusion: Tissue Doppler Imaging is a reliable, accurate and easily reproducible modality of echocardiography. The reduced peak systolic velocity and reduced peak early diastolic velocity seems to be an expression of regionally reduced systolic and diastolic functions, respectively. While the reduced mean systolic velocity and reduced mean early diastolic velocity from 4 mitral annulus sites are expressions of globally reduced systolic and diastolic functions, respectively and were correlated well with the ejection fraction. Keywords: Tissue Doppler imaging, ejection fraction, peak systolic velocity, peak early diastolic velocity, deceleration time, isovolumic relaxation time